STRES DAN SELF EFFICACY KADAR GULA DARAH PADA PASIEN DIABETES MELITUS - Lismawati Pertiwi Waruwu Lisa; Ismed Krisman Amazihono; Hadirat Candra Laoli (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
Diabetes mellitus not only causes premature death worldwide, it is also a major causeof blindness, heart disease and kidney failure. The International Organization for Diabetes Federations (IDF) estimates that there are at least 463 million people aged 20-79 years in the world suffering from diabetes in 2019 or equivalent to a prevalence rate of 9.3% of the total population at the same age.Stress is a non-specific body response to any disturbed need, a universal phenomenon that occurs in everyday life and cannot be avoided, everyone experiences it, stress has a total impact on every individual, namely physical, psychological, intellectual, social and spiritual. , Stress can threaten psychological balance. One of the causes of increased sugar levels is stress levels. Stress can also disrupt the endocrine system so that it can cause blood sugar levels to increase.Feelings of fear, anxiety, shame and anger are other forms of emotional life filled with stress that will affect blood glucose fluctuations even though diet, physical exercise and drug use are as carefully as possible. Often due to stress, people with Diabetes Mellitus will violate the diet program, rarely exercising, not regularly taking medication and rarely controlling blood sugar levels, proves that people with diabetes mellitus when under stress cannot organize selfefficacy properly. According to Notoadmodjo, self-efficacy affects one's behavior towards compliance. Self-efficacy is an individual's belief in his ability to organize and perform certain tasks needed to get the expected results.The purpose of this study was to analyze the relationship between stress levels and selfefficacy on blood sugar levels in diabetes mellitus patients at the UPTD Hiliduho Health Center Nias Regency in 2022. So that DM patients can reduce and control stress levels and further increase self-efficacy so that blood sugar ranges are always within normal limits. . The results showed that there was a significant relationship between stress and blood sugar levels, p value = 0.002 <0.005 and a significant relationship between self-efficacy and blood sugar levels, p value = 0.000 <0.005.